Differential response of the thyroid axis to high-fat diet-induced inflammation and energy balance deregulation in juvenile and adult rats - Alvarez-Salas, Elena; Soberanes-Chávez, Paulina; Andrade, Alicia; Dolores-SanJuan, Juan Luis; García-Luna, Cinthia; Matamoros-Trejo, Gilberto; de Gortari, Patricia (Frontiers in Endocrinology, 2025)
IntroductionThe hypothalamic–pituitary–thyroid (HPT) axis regulates metabolic rate and adapts to fluctuations in energy demand, through changing the expression of thyrotropin releasing hormone (TRH) in the hypothalamic paraventricular nucleus (PVN), which drives those neuroendocrine responses. TRHergic neurons integrate multiple signals, including those arising from infections and dietary energy challenges. High-fat diet (HFD) intake, for example, activates PVN TRH mRNA and the HPT axis to manage energy excess; also, it promotes interleukin-1β (IL-1β)-mediated neuroinflammation disrupting axis function. How HPT axis adapts to simultaneous metabolic and inflammatory stimuli across development and under different durations of HFD exposure remains unelucidated.MethodsWe investigated these interactions in juvenile (21 days old) and adult (2.5 months old) Wistar rats exposed to HFD for 4 or 12 weeks.ResultsOur findings showed that the longer the HFD exposure and the younger the animals, the greater the impairment of HPT axis function and body weight (b.w.) regulation. Short-term HFD feeding revealed age-dependent effects on b.w. since only juveniles were heavier than their controls, while the HPT axis was active on both. Neuroinflammatory responses also differed by developmental stage and duration. After 4 weeks of HFD, only juveniles displayed elevated IL-1β protein expression, whereas after 12 weeks, both age groups exhibited increased IL-1β; however, adults remained more resilient to cytokine overexpression than juveniles, regarding HPT axis function.DiscussionProlonged exposure promoted IL-1β–associated neuroinflammation, altered HPT axis regulation and favored leptin resistance, particularly in juveniles. These results highlighted the critical role of developmental stage and diet duration in HFD intake neuroendocrine effects.